Gambaran Perilaku Penderita Hipertensi dalam Manajemen Diet di Puskesmas Singkarak Kabupaten Solok Tahun 2023 - Yulastri, Yulastri; Zulharmaswita, Zulharmaswita; Deswita, Desi; Mirawati, Anita; Azhar, Dini Amalia (Jurnal Keperawatan Sehat Mandiri, 2023)
Hypertension is a non-communicable disease and has a fairly high mortality rate and affects a person's quality of life and productivity. It is estimated that by 2025 there will be 1.5 billion people affected by hypertension, and it is estimated that every year 10.44 million people die from hypertension and its complications. The purpose of this study was to describe the behavior of hypertension sufferers in diet management at the Singkarak Health Center, Solok Regency, in 2023. The design in this research is descriptive. The population in this study were all hypertensive patients diagnosed with hypertension at the Singkarak Health Center, Solok Regency, aged 18 to 59 years. The sampling technique used the Simple Random Sampling technique with a total sample of 68 samples. Data was collected from May 2 to May 12 2023 by means of interviews and the tool used was a questionnaire. Data were processed manually and then analyzed univariately using descriptive statistics. The results of this study indicate that most (61.8%) of respondents included good knowledge, most (67.6%) of respondents put a positive position, and almost all (86.8%) of respondents included their actions in diet management. It is hoped that the Singkarak Health Center can increase counseling activities and provide information for hypertension sufferers who have not been exposed to health information.